PENGARUH KARAKTERISTIK INDIVIDU, PERLINDUNGAN HAK PEREMPUAN TERHADAP KUALITAS PELAYANAN KOMNAS PEREMPUAN DENGAN KOMPETENSI SUMBER DAYA MANUSIA SEBAGAI VARIABEL MEDIASI - Arliman S, Laurensius; Veri, Isdal; Gustiwarni, Gustiwarni; Elfitrayenti, Elfitrayenti; Sakurawati, Ade; Yasri, Yasri (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2020)
Abstract: The purpose of this study was to determine the effect of individual characteristics on the quality of services in Komnas Perempuan, protection of women's rights to service quality in Komnas Perempuan, individual characteristics of human resource competencies in Komnas Perempuan, human resource competencies on service quality in Komnas Perempuan, protection of women's rights to human resource competencies in Komnas Perempuan, human resource competencies in mediating the relationship between characteristics and quality of services in Komnas Perempuan, and human resource competencies mediating the relationship between protecting women's rights and the quality of services protecting women rights in Komnas Perempuan. Based on the formulation, objectives and research hypotheses, the method used in this study is quantitative research with a descriptive approach. Descriptive approach can be interpreted as a research method that seeks. The results found that the individual characteristics variable had a significant effect on the human resource variables of the National Commission on Violence Against Women employees. The variable on the protection of women's rights has a significant effect on the human resource variable of the National Commission's female employees. Individual Characteristics Variable has a significant effect on service quality variables in the National Commission on Violence Against Women. The variable of human resources has a significant effect on the variable service quality of employees. The variable on the protection of women's rights has a significant effect on the variable service quality of employees. 6) Characteristic variable does not significantly influence Service Quality through human resource construct variables. 7) The variable for the protection of women's rights does not significantly influence the Quality of Service through the human resource construct variable. Keywords: Human Resources, Mediation, Komnas Perempuan.